Handbook of international futurism - Berghaus, Günter (Berlin ; Boston : De Gruyter, 2019)
The Handbook of International Futurism is the first reference work ever to presents in a comparative fashion all media and countries in which the movement, initiated by F.T. Marinetti in 1909, exercised a particularly noteworthy influence. The handbook offers a synthesis of the state of scholarship regarding the international radiation of Futurism and its influence in some fifteen artistic disciplines and thirty-eight countries. While acknowledging the great achievements of the movement in the visual and literary arts of Italy and Russia, it treats Futurism as an international, multidisciplinary phenomenon that left a lasting mark on the manifold artistic manifestations of the early twentieth-century avant-garde. Hundreds of artists, who in some phase in their career absorbed Futurist ideas and stylistic devices, are presented in the context of their national traditions, their international connections and the media in which they were predominantly active. The handbook acts as a kind of multi-disciplinary, geographical encyclopaedia of Futurism and gives scholars with varying levels of experience a detailed overview of all countries and disciplines in which the movement had a major impact.
The Historiography of Italian Futurism / Berghaus, Günter -- The Politics of Futurism / Erjavec, Aleš -- Women Futurists / Re, Lucia / Douglas, Charlotte -- Architecture / Sabatino, Michelangelo -- Ceramics / Fochessati, Matteo -- Cinema / Strauven, Wanda -- Cuisine / Novero, Cecilia -- Dance / Veroli, Patrizia -- Fashion Design / Zoccoli, Franca / Lazareva, Ekaterina -- Graphic Design, Typography and Artists' Books / Bury, Stephen -- Decorative Arts, Furniture and Interior Design / Ruta, Anna Maria -- Music / Lombardi, Daniele -- Photography / Braun, Marta -- Radio and Sound Art / Fisher, Margaret -- Theatre / Pietropaolo, Domenico / Braun, Edward -- Visual Poetry / Rasula, Jed -- Argentina / Sarabia, Rosa -- Armenia / Beledian, Krikor -- Belgium / den Bossche, Bart Van -- Brazil / de Castro Rocha, João Cezar -- Bulgaria / Dell' Agata, Giuseppe -- Chile / Dawes, Greg -- China / Hu, Man -- The Czech Lands / Pomajzlová, Alena -- Denmark / Jelsbak, Torben / Stounbjerg, Per -- Egypt / Paniconi, Maria Elena / Radwan, Nadia -- Estonia / Hennoste, Tiit -- Finland / Riikonen, Hannu K. -- France / Bohn, Willard -- Georgia / Tsipuria, Bela -- Germany / Chytraeus-Auerbach, Irene -- Great Britain / Black, Jonathan -- Greece / Michaelides, Chris -- Hungary / Kappanyos, András -- Ireland / Daly, Selena -- Iceland / Hjartarson, Benedikt -- Italy / Somigli, Luca / Di Genova, Giorgio -- Japan / Zanotti, Pierantonio -- Korea / Cho, Kyoo Yun -- Latvia / Brasliņa, Aija -- Lithuania / Rachlevičiūtė, Ramutė -- Mexico / Moya, Sergio Delgado -- The Netherlands / van Kalmthout, Ton -- Peru / García, Carlos -- Poland / Strożek, Przemysław -- Portugal / Júdice, Nuno -- Romania / Cărăbaş, Irina -- Russia / Baran, Henryk / Lodder, Christina -- Spain / Anderson, Andrew A. -- Sweden / Olsson, Jesper -- Ukraine / Ilnytzkyj, Oleh S. -- Uruguay / Rocca, Pablo -- United States of America / Merjian, Ara H. / Lucchi, Nicola -- Venezuela / Montenegro, Giovanna -- The Former Yugoslavia and Its Republics Slovenia, Croatia and Serbia / Subotić, Irina / Vrečko, Janez / Roić, Sanja / Jović, Bojan / Čubrilo, Jasmina.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Jan 2019).
Includes bibliographical references and index.
Added to collection customer.56279.3
Keywords: Futurism (Art) -- Handbooks, manuals, etc; Futurism (Literary movement) -- Handbooks, manuals, etc; 20th century avant-garde art and literature; cross-fertilization in the arts; Futurism; Futurism (Art); Futurism (Literary movement); Electronic books